1994
DOI: 10.1037/0735-7036.108.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Rat (Rattus norvegicus) defensive behavior in total darkness: Risk-assessment function of defensive burying.

Abstract: Although rats (Rattus norvegicus) spend much of their lives in the darkness of burrows, defensive behavior in the dark has rarely been studied. We compared rats' reactions to aversive stimuli in dark and lighted 2-alley, burrowlike environments. Experiment 1 assessed reactions to an unsignaled airblast; Experiment 2 assessed neophobic reactions to an unfamiliar steel ball. Half of the rats were tested in light and half, in total darkness. In both experiments rats directed defensive burying and stretched approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…These actions, and also a specific “stretched attend” posture involving a lowering of the body and locomotion interspersed with periods of immobility during later forays onto the surface, were given the label “risk assessment activities” as they were hypothesized to represent attempts to determine if a threat was present, and to localize and possibly identify it, while remaining as safe as possible. Other activities, such as burying [56] or tossing substrate at [57] novel or ambiguously threatening stimuli have been included under this functional grouping, in that these appear to represent attempts to determine if this stimulus is alive, thus responsive to being buried or hit. An additional defensive behavior noted in the initial VBS study was behavioral inhibition, involving suppression or reduction of normal activities such as eating, drinking, sexual activity or aggression.…”
Section: Visible Burrow Systemmentioning
confidence: 99%
“…These actions, and also a specific “stretched attend” posture involving a lowering of the body and locomotion interspersed with periods of immobility during later forays onto the surface, were given the label “risk assessment activities” as they were hypothesized to represent attempts to determine if a threat was present, and to localize and possibly identify it, while remaining as safe as possible. Other activities, such as burying [56] or tossing substrate at [57] novel or ambiguously threatening stimuli have been included under this functional grouping, in that these appear to represent attempts to determine if this stimulus is alive, thus responsive to being buried or hit. An additional defensive behavior noted in the initial VBS study was behavioral inhibition, involving suppression or reduction of normal activities such as eating, drinking, sexual activity or aggression.…”
Section: Visible Burrow Systemmentioning
confidence: 99%
“…In these situations, rats will leave the nesting area using a stretched approach behavior. It has been speculated that the stretch approach posture may provide an opportunity for information gathering and risk assessment (Pinel et al 1994). The innate tests of anxiety described above (light-dark box, open field, elevated plus maze) are easily integrated into the pre-encounter-defensive phase as they all relate to exploration in a potentially dangerous environment.…”
Section: Predatory Imminence Theorymentioning
confidence: 99%
“…It has long been suggested that defensive responses are more efficiently learned when they are consistent with the natural repertoire of the animal [4]. Burrowing is a commonly observed defensive behavior in Rattus norvegicus [3, 20, 33, 35]. It was thus expected that entering a short tunnel would be an effective escape/avoidance response to light.…”
mentioning
confidence: 99%